Faktor-Faktor yang Mempengaruhi Pembelajaran Menulis pada Pendidikan Dasar dan Menengah - Anita Candra Dewi (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Writing learning is a productive language skill that plays a crucial role in developing students' critical, creative, and systematic thinking skills at the elementary and secondary levels. However, the practice of writing learning still faces various challenges influenced by internal and external factors. This study aims to comprehensively analyze the factors influencing writing learning based on a review of the latest literature. The method used is a literature study with a descriptive analytical approach to reputable national and international journal articles relevant to writing learning. Data sources were obtained through searches of scientific databases such as Google Scholar, ERIC, and Scopus with publications spanning the last ten years. Data analysis was conducted thematically by grouping research findings into internal and external factors. The results of the study indicate that internal factors include language ability, intrinsic motivation, and student creativity, while external factors include teacher teaching strategies, feedback quality, the learning environment, and the use of digital media and technology. The interaction between internal and external factors has been shown to play a significant role in determining the success of writing learning. Effective writing learning requires a holistic approach that integrates strengthening language skills, increasing student motivation and creativity, and the application of adaptive and technology-based pedagogical strategies. The findings of this study are expected to provide a theoretical and practical foundation for educators in designing meaningful and relevant writing lessons to meet the demands of 21st-century education.